MUTU SELAI DARI KOMBINASI BUAH NANAS DAN KELOPAK ROSELLA - Agus Anjar Sumantri Samosir; Usman Pato; Vonny Setiaries Johan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Fruit jam is a semi-wet food processed  product from a mixture of fruit juice and  sugar. The purpose of this research was to evaluate the effect of ratio of pineapple and rosella petals on the jam quality. This research used a Completely Randomized Design experiment with five treatments and three replications. The  treatments were NR1 (pineapple puree and rosella petal puree 90:10), NR2 (pineapple puree and rosella petal puree  80:20), NR3 (pineapple puree and rosella petal puree 70:30) and NR4 (pineapple puree and rosella petal puree 60:40) and NR5 (pineapple puree and rosella petal puree 50:50). The value of observation were analyzed using Analysis of Varians followed by Duncan’s New Multiple Range Test on 5% level. The result showed that the ratio of pineaple and rosella petals puree significantly affected  the moisture, total dissolved solid, ash , pectin and sucrose contents, antioxidant activity, descriptive test of color, flavour, taste and texture. The best treatment was NR1 with moisture content 29.21%, total dissolved solids 89.80%, ash content 0.36%, pectin  1.62%, sucrose 57.34% and antioxidant activity 25.31 ppm, dark red color, flavourful pineapple and rosella, pineapple taste, soft texture of jam.Keywords: Jam, pineapple, rosella petal.